States and Welfare States Government for the People. - Spicker, Paul (Policy Press, 2022)
Most governments in the world have taken responsibility for social policy and elected to develop services in health, education and social security. This book explores the role of government and the state in the contemporary world and discusses views about government responsibility for social welfare services.